Pengaruh Co-Branding dan Content Marketing Terhadap Brand Awareness Film Sore: Istri Dari Masa Depan X Parfum HMNS (Studi pada Mahasiswa di Kota Malang) - Putri, Viola Prisilia; Santoso, Eko Boedhi (Teewan Journal Solutions, 2026)
The growth of the creative industry and local brands in Indonesia has encouraged industry players to integrate innovative digital marketing strategies to maintain competitiveness. Amid information overload conditions, building brand awareness in the minds of consumers has become a significant challenge. The collaboration between Film Sore: Istri dari Masa Depan and HMNS Perfume implements a co-branding strategy communicated through content marketing on social media as an effort to strengthen brand awareness. This study aimed to analyze the influence of co-branding and content marketing on brand awareness of the Film Sore: Istri dari Masa Depan and HMNS Perfume collaboration among college students in Malang City. This research is an explanatory study with a quantitative approach. The purposive sampling technique obtained 100 respondents from college students in Malang City. The data analysis method used was multiple linear regression analysis along with hypothesis testing. The t-test results showed that co-branding (X1) and content marketing (X2) have a partial influence on brand awareness (Y). Based on the F-test results, co-branding and content marketing simultaneously have a significant influence on brand awareness. It is recommended that HMNS and the production house of Film Sore maintain conceptual alignment in their co-branding strategy and improve the quality of content marketing on social media.